5 myths about women in the New Testament period - Hylen, Susan E. (The Biblical archaeology review, 2020)
Modern readers of the New Testament often imagine that women’s lives in the first and second centuries C.E. were highly restricted. This mind-set has led to a number of myths concerning women and their condition in first-century Roman Judea, or what many call the New Testament period. While women were not considered the equals […]